Tathwīr Mawād Ta’līm al-Lughah al-‘Arabiyyah al-I’lāmiyyah li Thullāb Syu’bah Ta’līm al-Lughah al-‘Arabiyyah bi Jāmi’ah Malang al-Hukumiyyah - Shovi Maryam; Nasaruddin Idris Jauhar; Junaedi Junaedi (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2022)
This study aimed to (1) develop teaching book of Journalistic Arabic for students of the Division of Arabic Education at State University of Malang, and (2) measure the effectiveness of the book. The researcher used the type of research “Research and development, and this research and development is based on the model of Sugiyono. The study used qualitative approach and quantitative approach. The analyses qualitative data by using Miles and Huberman’s theory, and analyses quantitative data by using T-Test and Likert scale. This study developed the book from the materials on website Indonesiaalyoum.com. The results of this study are following (a) Development of teaching book of Journalistic Arabic  for students of the Division of Arabic Teaching at State University of Malang was done in ten steps. Assessment of the materials developed by experts and lecturers was rated "very good", and by students it was rated "excellent" which is eligible to be used in teaching and (b) based on data analysis for the pre-test and post-test in the first and field trial using SPSS t-test program indicates that the calculated t-result is greater than the table t-result. Thus, the developed teaching book is effective in improving the grades of students.